Determining T2 relaxation time and stroke onset relationship in ischaemic stroke within apparent diffusion coefficient-defined lesions. A user-independent method for quantifying the impact of stroke in the human brain - Knight, M; Damion, R; McGarry, B; Bosnell, R; Jokivarsi, K; Gröhn, O; Jezzard, P; Harston, G; Carone, D; Kennedy, J; El-Tawil, S; Elliot, J; et al. (IOS Press, 2019)
Background and objective:In hyperacute ischaemic stroke, T2 of cerebral water increases with time. Quantifying this change may be informative of the extent of tissue damage and onset time. Our objective was to develop a user-unbiased method to measure the effect of cerebral ischaemia on T2 to study stroke onset time-dependency in human acute stroke lesions. Methods:Six rats were subjected to permanent middle cerebral occlusion to induce focal ischaemia, and a consecutive cohort of acute stroke patients (n=38) were recruited within 9 hours from symptom onset. T1-weighted structural, T2 relaxometry, and diffusion MRI for apparent diffusion coefficient (ADC) were acquired. Ischaemic lesions were defined as regions of lowered ADC. The median T2 difference (ΔT2) between lesion and contralateral non-ischaemic control region was determined by the newly-developed spherical reference method, and data compared to that obtained by the mirror reference method. Linear regressions and receiver operating characteristics (ROC) were compared between the two methods. Results:ΔT2 increases linearly in rat brain ischaemia by 1.9 ± 0.8 ms/h during the first 6 hours, as determined by the spherical reference method. In patients, ΔT2 linearly increases by 1.6 ± 1.4 and 1.9 ± 0.9 ms/h in the lesion, as determined by the mirror reference and spherical reference method, respectively. ROC analyses produced areas under the curve of 0.83 and 0.71 for the spherical and mirror reference methods, respectively. Conclusions:Data from the spherical reference method showed that the median T2 increase in the ischaemic lesion is correlated with stroke onset time in a rat as well as in a human patient cohort, opening the possibility of using the approach as a timing tool in clinics.